PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA V CABANG KEBUN INTI KECAMATAN TAPUNG KABUPATEN KAMPAR - -, Nuraini; Indarti, Sri; -, Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study is to find out the impact of environment and motivation to employee productivity in PT. Perkebunan Nusantara V Kebun Inti Kecamatan Tapung Kabupaten Kampar in partially and simultanously. The research population are all employee fror production division of PT. Perkebunan Nusantara V Kebun Inti Kecamatan Tapung Kabupaten Kampar for amount of 259 peoples. To determine the sample’s amount is use the Slovin formula. Samples were 157 people, taken by the cluster sampling method while to determine sample is use purposive sampling. To analyze the data are use multiple regression model. According to the study, environment and motivation are simultanously have a significant effect to the emloyee productivity of PTPN Kebun Inti Kecamatan Tapung Kabupaten Kampar. To improve the employee productivity, the management have to take a more interrest to the implementation og motivation and environment. Environtment and motivation partially has a significant effect to the employee productivity at Kebun Inti Kecamatan Tapung Kabupaten Kampar. Motivation has a dominant effect to productivity than the environment. Keyword : Environment, Motivation, Productivity